Heat-insulating and scratch-resistant car cover film and preparation method thereof

By using a double-layer hollow mesh and nanocomposite unit design in the car coat film, the shortcomings of the existing car coat film in terms of thermal insulation and scratch resistance are solved, and higher thermal insulation and scratch resistance are achieved.

CN119735941APending Publication Date: 2025-04-01SUZHOU AOBEIXIN MATERIAL TECH LTD CO
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411871773.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing car coat film has shortcomings in terms of heat insulation and scratch resistance, and the preparation process is cumbersome.

Method used

A double-layer hollow mesh is used as the substrate. The mesh fibers are composed of Elosite nanotubes and silica. Combined with the nano-hollow tube lumen structure, the heat insulation effect is increased, and negative expansion is caused by the nanocomposite unit during scratching or friction, enhancing scratch resistance.

Benefits of technology

It significantly improves the thermal insulation effect and scratch resistance of the car coat film, enhances the stability and impact resistance of the car coat film, and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a heat-insulating and scratch-resistant car cover film and a preparation method thereof. The heat-insulating and scratch-resistant car cover film uses thermoplastic polyurethane as a substrate and a double-layer hollow mesh loaded with nano-titanium dioxide as a filler; the double-layer hollow mesh loaded with nano-titanium dioxide uses halloysite nanotubes as a raw material, is prepared by electrospinning and then loaded with nano-titanium dioxide. The present invention adopts a double-layer hollow mesh, the mesh fiber is single-layer hollow, and combined with the unique nano hollow tube cavity structure of the halloysite nanotubes in the fiber, a double-layer hollow structure is formed, which greatly improves the heat insulation effect; the mesh fiber is composed of halloysite nanotubes and silicon dioxide, and can form a nano-composite unit. When the car cover is scratched or rubbed, the friction heat generated loses the water molecules in its structure, resulting in size shrinkage, causing negative expansion, making the car cover structure more compact, and forming compressive stress on the surface of the car cover, which can effectively inhibit the generation of cracks, thereby improving the scratch resistance of the car cover.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional film materials, and in particular to a heat-insulating and scratch-resistant car cover film and a preparation method thereof. Background Art

[0002] The so-called car film is a layer of film attached to the car paint to protect or change the color of the car paint. Therefore, it is also divided into paint protection film and color change film. The material used is generally TPU (thermoplastic elastomer of polyurethane) or PVC (polyvinyl chloride). The paint protection film needs to have long-term super toughness and wear resistance, collision resistance, and transparency. After installation, the car paint surface is isolated from the air, thereby playing a role in preventing acid rain, oxidation, and scratches. The paint protection film is generally composed of a substrate, glue, a base material (also called a base film), a self-repairing coating, and a PET protective film. The substrate is the part used to protect the adhesive layer from production to mounting; the glue is used to connect the protective film to the car paint surface, and different formulas are adjusted to optimize the installation convenience and the fit after mounting; the substrate (also called the base film) is the main body of the product, which plays a role in supporting the frame structure. It is mainly made of polyurethane thermoplastic elastomer (TPU) or polyvinyl chloride (PVC), among which TPU material is more impact-resistant, UV-resistant, easy to stretch, and aging-resistant; the self-repairing coating is attached to the outermost side, and is modulated by a special formula to have a cross-linked network structure, thereby achieving brightening, stain resistance, hydrophobicity, thermal repair and other functions; the PET protective film is used to protect the transparent coating from production to mounting. At present, the car cover film is usually composed of multiple layers as above, which is relatively cumbersome, and the heat insulation effect and scratch resistance are not good. Summary of the invention

[0003] Technical problem to be solved: In view of the above technical problems, the purpose of the present invention is to provide a heat-insulating and scratch-resistant car cover film and a preparation method thereof, which adopts a double-layer hollow mesh membrane, in which the mesh fibers are single-layer hollow, and combined with the unique nano hollow tube cavity structure of halloysite nanotubes in the fibers, a double-layer hollow structure is formed, which greatly improves the heat insulation effect; the mesh fibers are composed of halloysite nanotubes and silica, and can form nano-composite units. When the car cover is scratched or rubbed, the friction heat generated will lose the water molecules in its structure, resulting in size shrinkage, causing negative expansion, making the car cover structure denser, and forming compressive stress on the surface of the car cover, which can effectively inhibit the generation of cracks and reduce the shear stress between the car cover and the car paint during scratching or friction, thereby improving the scratch resistance of the car cover.

[0004] Technical solution: A heat-insulating and scratch-resistant car cover film, which uses thermoplastic polyurethane as a substrate and a double-layer hollow mesh membrane loaded with nano-titanium dioxide as a filler; The mass ratio of the thermoplastic polyurethane to the double-layer hollow mesh membrane loaded with nano-titanium dioxide is 12:(5-7); The double-layer hollow mesh membrane loaded with nano-titanium dioxide is prepared by electrostatic spinning with halloysite nanotubes as raw materials and then loaded with nano-titanium dioxide. Furthermore, the heat-insulating and scratch-resistant car cover film also includes antioxidants, and the antioxidants are antioxidant 245, antioxidant 1010, antioxidant 1076 and antioxidant 3114. Furthermore, the thickness of the heat-insulating and scratch-resistant car cover film is 200-400 μm. Furthermore, the preparation method of the double-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows, in parts by weight: Step 1: Mix 20 parts of N-methylpyrrolidone, 5 parts of polyvinylpyrrolidone and 70 parts of halloysite nanotubes and stir them evenly to obtain a halloysite nanotube dispersion; Step 2: Mix ethyl orthosilicate and ethanol, add hydrochloric acid, stir and hydrolyze for 30 minutes to obtain a transparent solution; Step 3: Add the halloysite nanotube dispersion, mix and stir evenly to obtain a shell solution; Step 4: Take 90% N-methylpyrrolidone aqueous solution as the core layer solution; Step 5: Perform electrospinning using a coaxial electrospinning device to obtain an electrospinning membrane; Step 6: Take out and dry, place in a programmed temperature furnace for calcination, heat to 650-700°C at 3°C / min and keep at this temperature for 3h, then continue to heat to 900-1000°C at a rate of 5 / min°C and keep at this temperature for 3h; Step 7: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain double-layer hollow membrane particles; Step 8: Take 10 portions of double-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 9: Add 1-1.5 parts of nano-titanium dioxide and 20 parts of ultrapure water, stir and mix with ultrasound at 40°C and 150W for 1 hour, let stand at room temperature for 12 hours, and dry to obtain a double-layer hollow mesh membrane loaded with nano-titanium dioxide. Furthermore, the molar ratio of tetraethyl orthosilicate, ethanol and hydrochloric acid is 1:11:4.6. Furthermore, the volume ratio of the transparent solution to the halloysite nanotube dispersion is 1:(1-2). Furthermore, the electrospinning conditions are: voltage of 20 kV, humidity of 60%, outer diameter of shell needle of 1.4 mm, inner diameter of 1.2 mm, outer diameter of core needle of 1.0 mm, inner diameter of 0.7 mm, and distance from receiving plate of 20 cm. Furthermore, in step 5, the thickness of the electrospinning membrane is 45-55 μm. The method for preparing the heat-insulating and scratch-resistant car cover film is characterized by comprising the following steps, measured in parts by weight: S1: Mix thermoplastic polyurethane, a double-layer hollow mesh membrane loaded with nano-titanium dioxide and an antioxidant, and place them in an internal mixer for extrusion mixing at 160°C; S2: Put it into a screw extruder, extrude it, and then perform tape casting to obtain it. Furthermore, the screw extrusion conditions are as follows: the temperature from the feeding end to the die is 50-80°C, 80-145°C, 145-200°C, 180-245°C, 180-220°C and 170-210°C, and the screw speed is 25-40rpm. Beneficial effects: 1. The present invention adopts a double-layer hollow mesh, and the mesh fiber is single-layer hollow, combined with the unique nano hollow tube structure of the halloysite nanotubes in the fiber, thus forming a double-layer hollow structure, which greatly improves the thermal insulation effect. 2. The mesh fibers in the present invention are composed of halloysite nanotubes and silica, which can form nanocomposite units. When the car cover is scratched or rubbed, the friction heat generated will cause the car cover to lose water molecules in its structure, resulting in size shrinkage and negative expansion, making the car cover structure denser and forming compressive stress on the surface of the car cover, which can effectively inhibit the generation of cracks and reduce the shear stress between the car cover and the car paint during scratching or friction, thereby improving the scratch resistance of the car cover. 3. The active chemical bonds of the halloysite nanotubes in the present invention can easily load nano-titanium dioxide, making it more evenly dispersed and avoiding the phenomenon of agglomeration when directly added into polyurethane. 4. The present invention uses a double-layer hollow mesh (a ceramic mesh with very high hardness) as a support to improve the stability of the car cover film. The nano-titanium dioxide loaded thereon forms a chemical bond with the mesh molecules, effectively transferring the load. It can stretch, slide, and absorb energy when subjected to load, thereby inhibiting the initiation and expansion of cracks in the car cover film, and at the same time can improve the tensile strength, fracture toughness and impact resistance of the car cover. 5. The presence of nano titanium dioxide in the present invention can, on the one hand, realize photocatalytic degradation of pollutants and achieve a self-cleaning effect. At the same time, its presence can also absorb and disperse stress, reduce stress concentration, thereby delaying the accumulation of fatigue damage to the car cover and extending its service life. DETAILED DESCRIPTION The present invention proposes a heat-insulating and scratch-resistant car cover film and a preparation method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention will be further described in detail with reference to the following examples. It should be understood that the specific examples described herein are only used to explain the present invention and are not used to limit the present invention. Example 1 A method for preparing a heat-insulating and scratch-resistant car cover film comprises the following steps, measured in parts by weight: S1: 12 parts of thermoplastic polyurethane, 6 parts of double-layer hollow mesh membrane loaded with nano-titanium dioxide and 0.03 parts of antioxidant 1076 were mixed, placed in an internal mixer and extruded and mixed at 160°C; S2: put it into a screw extruder for extrusion. The screw extrusion conditions are as follows: the temperature from the feeding end to the die head is 65°C, 120°C, 180°C, 220°C, 220°C and 190°C respectively, the screw speed is 30rpm, and the film is cast to obtain a heat-insulating and scratch-resistant car cover film with a thickness of 300μm. The preparation method of the double-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows: Step 1: 20 g of N-methylpyrrolidone, 5 g of polyvinylpyrrolidone and 70 g of halloysite nanotubes were mixed and stirred to obtain a halloysite nanotube dispersion; Step 2: Mix ethyl orthosilicate and ethanol, add hydrochloric acid, stir and hydrolyze for 30 minutes to obtain a transparent solution; Step 3: adding the halloysite nanotube dispersion, mixing and stirring evenly to obtain a shell solution; the molar ratio of ethyl orthosilicate, ethanol and hydrochloric acid is 1:11:4.6; the volume ratio of the transparent solution to the halloysite nanotube dispersion is 1:1; Step 4: Take 90% N-methylpyrrolidone aqueous solution as the core layer solution; Step 5: electrospinning was performed using a coaxial electrospinning device. The electrospinning conditions were: voltage 20 kV, humidity 60%, outer diameter of the shell needle 1.4 mm, inner diameter 1.2 mm, outer diameter of the core needle 1.0 mm, inner diameter 0.7 mm, and a distance of 20 cm from the receiving plate to obtain an electrospinning membrane with a thickness of 50 μm. Step 6: Take out and dry, place in a programmed temperature furnace for calcination, heat to 650°C at a rate of 3°C / min and keep at that temperature for 3h, then continue to heat to 950°C at a rate of 5°C / min and keep at that temperature for 3h; Step 7: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain double-layer hollow membrane particles; Step 8: Take 10 g of double-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 9: Add 1.3 g of nano-titanium dioxide and 20 mL of ultrapure water, stir and mix with ultrasound at 40°C and 150 W for 1 h, let stand at room temperature for 12 h, and dry to obtain a double-layer hollow mesh membrane loaded with nano-titanium dioxide. Example 2 A method for preparing a heat-insulating and scratch-resistant car cover film comprises the following steps, measured in parts by weight: S1: 12 parts of thermoplastic polyurethane, 6 parts of double-layer hollow mesh membrane loaded with nano-titanium dioxide and 0.03 parts of antioxidant 1076 were mixed, placed in an internal mixer and extruded and mixed at 160°C; S2: put it into a screw extruder for extrusion. The screw extrusion conditions are as follows: the temperature from the feeding end to the die head is 65°C, 120°C, 180°C, 220°C, 220°C and 190°C respectively, the screw speed is 30rpm, and the film is cast to obtain a heat-insulating and scratch-resistant car cover film with a thickness of 300μm. The preparation method of the double-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows: Step 1: 20 g of N-methylpyrrolidone, 5 g of polyvinylpyrrolidone and 70 g of halloysite nanotubes were mixed and stirred to obtain a halloysite nanotube dispersion; Step 2: Mix ethyl orthosilicate and ethanol, add hydrochloric acid, stir and hydrolyze for 30 minutes to obtain a transparent solution; Step 3: adding the halloysite nanotube dispersion, mixing and stirring evenly to obtain a shell solution; the molar ratio of ethyl orthosilicate, ethanol and hydrochloric acid is 1:11:4.6; the volume ratio of the transparent solution to the halloysite nanotube dispersion is 1:1.5; Step 4: Take 90% N-methylpyrrolidone aqueous solution as the core layer solution; Step 5: electrospinning was performed using a coaxial electrospinning device. The electrospinning conditions were: voltage 20 kV, humidity 60%, outer diameter of the shell needle 1.4 mm, inner diameter 1.2 mm, outer diameter of the core needle 1.0 mm, inner diameter 0.7 mm, and a distance of 20 cm from the receiving plate to obtain an electrospinning membrane with a thickness of 50 μm. Step 6: Take out and dry, place in a programmed temperature furnace for calcination, heat to 650°C at a rate of 3°C / min and keep at that temperature for 3h, then continue to heat to 950°C at a rate of 5°C / min and keep at that temperature for 3h; Step 7: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain double-layer hollow membrane particles; Step 8: Take 10 g of double-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 9: Add 1.3 g of nano-titanium dioxide and 20 mL of ultrapure water, stir and mix with ultrasound at 40°C and 150 W for 1 h, let stand at room temperature for 12 h, and dry to obtain a double-layer hollow mesh membrane loaded with nano-titanium dioxide. Example 3 A method for preparing a heat-insulating and scratch-resistant car cover film comprises the following steps, measured in parts by weight: S1: 12 parts of thermoplastic polyurethane, 6 parts of double-layer hollow mesh membrane loaded with nano-titanium dioxide and 0.03 parts of antioxidant 1076 were mixed, placed in an internal mixer and extruded and mixed at 160°C; S2: put it into a screw extruder for extrusion. The screw extrusion conditions are as follows: the temperature from the feeding end to the die head is 65°C, 120°C, 180°C, 220°C, 220°C and 190°C respectively, the screw speed is 30rpm, and the film is cast to obtain a heat-insulating and scratch-resistant car cover film with a thickness of 300μm. The preparation method of the double-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows: Step 1: 20 g of N-methylpyrrolidone, 5 g of polyvinylpyrrolidone and 70 g of halloysite nanotubes were mixed and stirred to obtain a halloysite nanotube dispersion; Step 2: Mix ethyl orthosilicate and ethanol, add hydrochloric acid, stir and hydrolyze for 30 minutes to obtain a transparent solution; Step 3: adding the halloysite nanotube dispersion, mixing and stirring evenly to obtain a shell solution; the molar ratio of ethyl orthosilicate, ethanol and hydrochloric acid is 1:11:4.6; the volume ratio of the transparent solution to the halloysite nanotube dispersion is 1:2; Step 4: Take 90% N-methylpyrrolidone aqueous solution as the core layer solution; Step 5: electrospinning was performed using a coaxial electrospinning device. The electrospinning conditions were: voltage 20 kV, humidity 60%, outer diameter of the shell needle 1.4 mm, inner diameter 1.2 mm, outer diameter of the core needle 1.0 mm, inner diameter 0.7 mm, and a distance of 20 cm from the receiving plate to obtain an electrospinning membrane with a thickness of 50 μm. Step 6: Take out and dry, place in a programmed temperature furnace for calcination, heat to 650°C at a rate of 3°C / min and keep at that temperature for 3h, then continue to heat to 950°C at a rate of 5°C / min and keep at that temperature for 3h; Step 7: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain double-layer hollow membrane particles; Step 8: Take 10 g of double-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 9: Add 1.3 g of nano-titanium dioxide and 20 mL of ultrapure water, stir and mix with ultrasound at 40°C and 150 W for 1 h, let stand at room temperature for 12 h, and dry to obtain a double-layer hollow mesh membrane loaded with nano-titanium dioxide. Example 4 A method for preparing a heat-insulating and scratch-resistant car cover film comprises the following steps, measured in parts by weight: S1: 12 parts of thermoplastic polyurethane, 6 parts of double-layer hollow mesh membrane loaded with nano-titanium dioxide and 0.03 parts of antioxidant 1076 were mixed, placed in an internal mixer and extruded and mixed at 160°C; S2: put it into a screw extruder for extrusion. The screw extrusion conditions are as follows: the temperature from the feeding end to the die head is 65°C, 120°C, 180°C, 220°C, 220°C and 190°C respectively, the screw speed is 30rpm, and the film is cast to obtain a heat-insulating and scratch-resistant car cover film with a thickness of 300μm. The preparation method of the double-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows: Step 1: 20 g of N-methylpyrrolidone, 5 g of polyvinylpyrrolidone and 70 g of halloysite nanotubes were mixed and stirred to obtain a halloysite nanotube dispersion; Step 2: Mix ethyl orthosilicate and ethanol, add hydrochloric acid, stir and hydrolyze for 30 minutes to obtain a transparent solution; Step 3: adding the halloysite nanotube dispersion, mixing and stirring evenly to obtain a shell solution; the molar ratio of ethyl orthosilicate, ethanol and hydrochloric acid is 1:11:4.6; the volume ratio of the transparent solution to the halloysite nanotube dispersion is 1:1.5; Step 4: Take 90% N-methylpyrrolidone aqueous solution as the core layer solution; Step 5: electrospinning was performed using a coaxial electrospinning device. The electrospinning conditions were: voltage 20 kV, humidity 60%, outer diameter of the shell needle 1.4 mm, inner diameter 1.2 mm, outer diameter of the core needle 1.0 mm, inner diameter 0.7 mm, and a distance of 20 cm from the receiving plate to obtain an electrospinning membrane with a thickness of 50 μm. Step 6: Take out and dry, place in a programmed temperature furnace for calcination, heat to 650°C at a rate of 3°C / min and keep at that temperature for 3h, then continue to heat to 950°C at a rate of 5°C / min and keep at that temperature for 3h; Step 7: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain double-layer hollow membrane particles; Step 8: Take 10 g of double-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 9: Add 1.0 g of nano-titanium dioxide and 20 mL of ultrapure water, stir and mix with ultrasound at 40°C and 150 W for 1 h, let stand at room temperature for 12 h, and dry to obtain a double-layer hollow mesh membrane loaded with nano-titanium dioxide. Example 5 A method for preparing a heat-insulating and scratch-resistant car cover film comprises the following steps, measured in parts by weight: S1: 12 parts of thermoplastic polyurethane, 6 parts of double-layer hollow mesh membrane loaded with nano-titanium dioxide and 0.03 parts of antioxidant 1076 were mixed, placed in an internal mixer and extruded and mixed at 160°C; S2: put it into a screw extruder for extrusion. The screw extrusion conditions are as follows: the temperature from the feeding end to the die head is 65°C, 120°C, 180°C, 220°C, 220°C and 190°C respectively, the screw speed is 30rpm, and the film is cast to obtain a heat-insulating and scratch-resistant car cover film with a thickness of 300μm. The preparation method of the double-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows: Step 1: 20 g of N-methylpyrrolidone, 5 g of polyvinylpyrrolidone and 70 g of halloysite nanotubes were mixed and stirred to obtain a halloysite nanotube dispersion; Step 2: Mix ethyl orthosilicate and ethanol, add hydrochloric acid, stir and hydrolyze for 30 minutes to obtain a transparent solution; Step 3: adding the halloysite nanotube dispersion, mixing and stirring evenly to obtain a shell solution; the molar ratio of ethyl orthosilicate, ethanol and hydrochloric acid is 1:11:4.6; the volume ratio of the transparent solution to the halloysite nanotube dispersion is 1:1.5; Step 4: Take 90% N-methylpyrrolidone aqueous solution as the core layer solution; Step 5: electrospinning was performed using a coaxial electrospinning device. The electrospinning conditions were: voltage 20 kV, humidity 60%, outer diameter of the shell needle 1.4 mm, inner diameter 1.2 mm, outer diameter of the core needle 1.0 mm, inner diameter 0.7 mm, and a distance of 20 cm from the receiving plate to obtain an electrospinning membrane with a thickness of 50 μm. Step 6: Take out and dry, place in a programmed temperature furnace for calcination, heat to 650°C at a rate of 3°C / min and keep at that temperature for 3h, then continue to heat to 950°C at a rate of 5°C / min and keep at that temperature for 3h; Step 7: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain double-layer hollow membrane particles; Step 8: Take 10 g of double-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 9: Add 1.5 g of nano-titanium dioxide and 20 mL of ultrapure water, stir and mix with ultrasound at 40°C and 150 W for 1 h, let stand at room temperature for 12 h, and dry to obtain a double-layer hollow mesh membrane loaded with nano-titanium dioxide. Example 6 A method for preparing a heat-insulating and scratch-resistant car cover film comprises the following steps, measured in parts by weight: S1: 12 parts of thermoplastic polyurethane, 5 parts of double-layer hollow mesh membrane loaded with nano-titanium dioxide and 0.03 parts of antioxidant 1076 were mixed, placed in an internal mixer and extruded and mixed at 160°C; S2: put it into a screw extruder for extrusion. The screw extrusion conditions are as follows: the temperature from the feeding end to the die head is 65°C, 120°C, 180°C, 220°C, 220°C and 190°C respectively, the screw speed is 30rpm, and the film is cast to obtain a heat-insulating and scratch-resistant car cover film with a thickness of 300μm. The preparation method of the double-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows: Step 1: 20 g of N-methylpyrrolidone, 5 g of polyvinylpyrrolidone and 70 g of halloysite nanotubes were mixed and stirred to obtain a halloysite nanotube dispersion; Step 2: Mix ethyl orthosilicate and ethanol, add hydrochloric acid, stir and hydrolyze for 30 minutes to obtain a transparent solution; Step 3: adding the halloysite nanotube dispersion, mixing and stirring evenly to obtain a shell solution; the molar ratio of ethyl orthosilicate, ethanol and hydrochloric acid is 1:11:4.6; the volume ratio of the transparent solution to the halloysite nanotube dispersion is 1:1.5; Step 4: Take 90% N-methylpyrrolidone aqueous solution as the core layer solution; Step 5: electrospinning was performed using a coaxial electrospinning device. The electrospinning conditions were: voltage 20 kV, humidity 60%, outer diameter of the shell needle 1.4 mm, inner diameter 1.2 mm, outer diameter of the core needle 1.0 mm, inner diameter 0.7 mm, and a distance of 20 cm from the receiving plate to obtain an electrospinning membrane with a thickness of 50 μm. Step 6: Take out and dry, place in a programmed temperature furnace for calcination, heat to 650°C at a rate of 3°C / min and keep at that temperature for 3h, then continue to heat to 950°C at a rate of 5°C / min and keep at that temperature for 3h; Step 7: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain double-layer hollow membrane particles; Step 8: Take 10 g of double-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 9: Add 1.3 g of nano-titanium dioxide and 20 mL of ultrapure water, stir and mix with ultrasound at 40°C and 150 W for 1 h, let stand at room temperature for 12 h, and dry to obtain a double-layer hollow mesh membrane loaded with nano-titanium dioxide. Example 7 A method for preparing a heat-insulating and scratch-resistant car cover film comprises the following steps, measured in parts by weight: S1: 12 parts of thermoplastic polyurethane, 7 parts of double-layer hollow mesh membrane loaded with nano-titanium dioxide and 0.03 parts of antioxidant 1076 were mixed, and the mixture was extruded and mixed in an internal mixer at 160°C; S2: put it into a screw extruder for extrusion. The screw extrusion conditions are as follows: the temperature from the feeding end to the die head is 65°C, 120°C, 180°C, 220°C, 220°C and 190°C respectively, the screw speed is 30rpm, and the film is cast to obtain a heat-insulating and scratch-resistant car cover film with a thickness of 300μm. The preparation method of the double-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows: Step 1: 20 g of N-methylpyrrolidone, 5 g of polyvinylpyrrolidone and 70 g of halloysite nanotubes were mixed and stirred to obtain a halloysite nanotube dispersion; Step 2: Mix ethyl orthosilicate and ethanol, add hydrochloric acid, stir and hydrolyze for 30 minutes to obtain a transparent solution; Step 3: adding the halloysite nanotube dispersion, mixing and stirring evenly to obtain a shell solution; the molar ratio of ethyl orthosilicate, ethanol and hydrochloric acid is 1:11:4.6; the volume ratio of the transparent solution to the halloysite nanotube dispersion is 1:1.5; Step 4: Take 90% N-methylpyrrolidone aqueous solution as the core layer solution; Step 5: electrospinning was performed using a coaxial electrospinning device. The electrospinning conditions were: voltage 20 kV, humidity 60%, outer diameter of the shell needle 1.4 mm, inner diameter 1.2 mm, outer diameter of the core needle 1.0 mm, inner diameter 0.7 mm, and a distance of 20 cm from the receiving plate to obtain an electrospinning membrane with a thickness of 50 μm. Step 6: Take out and dry, place in a programmed temperature furnace for calcination, heat to 650°C at a rate of 3°C / min and keep at that temperature for 3h, then continue to heat to 950°C at a rate of 5°C / min and keep at that temperature for 3h; Step 7: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain double-layer hollow membrane particles; Step 8: Take 10 g of double-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 9: Add 1.3 g of nano-titanium dioxide and 20 mL of ultrapure water, stir and mix with ultrasound at 40°C and 150 W for 1 h, let stand at room temperature for 12 h, and dry to obtain a double-layer hollow mesh membrane loaded with nano-titanium dioxide. Example 8 A method for preparing a heat-insulating and scratch-resistant car cover film comprises the following steps, measured in parts by weight: S1: 12 parts of thermoplastic polyurethane, 6 parts of double-layer hollow mesh membrane loaded with nano-titanium dioxide and 0.03 parts of antioxidant 1076 were mixed, placed in an internal mixer and extruded and mixed at 160°C; S2: put it into a screw extruder for extrusion. The screw extrusion conditions are as follows: the temperature from the feeding end to the die is 65°C, 120°C, 180°C, 220°C, 220°C and 190°C respectively, the screw speed is 30rpm, and the film is cast to obtain a heat-insulating and scratch-resistant car cover film with a thickness of 200μm. The preparation method of the double-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows: Step 1: 20 g of N-methylpyrrolidone, 5 g of polyvinylpyrrolidone and 70 g of halloysite nanotubes were mixed and stirred to obtain a halloysite nanotube dispersion; Step 2: Mix ethyl orthosilicate and ethanol, add hydrochloric acid, stir and hydrolyze for 30 minutes to obtain a transparent solution; Step 3: adding the halloysite nanotube dispersion, mixing and stirring evenly to obtain a shell solution; the molar ratio of ethyl orthosilicate, ethanol and hydrochloric acid is 1:11:4.6; the volume ratio of the transparent solution to the halloysite nanotube dispersion is 1:1.5; Step 4: Take 90% N-methylpyrrolidone aqueous solution as the core layer solution; Step 5: electrospinning was performed using a coaxial electrospinning device. The electrospinning conditions were: voltage 20 kV, humidity 60%, outer diameter of the shell needle 1.4 mm, inner diameter 1.2 mm, outer diameter of the core needle 1.0 mm, inner diameter 0.7 mm, and a distance of 20 cm from the receiving plate to obtain an electrospinning membrane with a thickness of 50 μm. Step 6: Take out and dry, place in a programmed temperature furnace for calcination, heat to 650°C at a rate of 3°C / min and keep at that temperature for 3h, then continue to heat to 950°C at a rate of 5°C / min and keep at that temperature for 3h; Step 7: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain double-layer hollow membrane particles; Step 8: Take 10 g of double-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 9: Add 1.3 g of nano-titanium dioxide and 20 mL of ultrapure water, stir and mix with ultrasound at 40°C and 150 W for 1 h, let stand at room temperature for 12 h, and dry to obtain a double-layer hollow mesh membrane loaded with nano-titanium dioxide. Example 9 A method for preparing a heat-insulating and scratch-resistant car cover film comprises the following steps, measured in parts by weight: S1: 12 parts of thermoplastic polyurethane, 6 parts of double-layer hollow mesh membrane loaded with nano-titanium dioxide and 0.03 parts of antioxidant 1076 were mixed, placed in an internal mixer and extruded and mixed at 160°C; S2: put it into a screw extruder for extrusion. The screw extrusion conditions are as follows: the temperature from the feeding end to the die is 65°C, 120°C, 180°C, 220°C, 220°C and 190°C respectively, the screw speed is 30rpm, and the film is cast to obtain a heat-insulating and scratch-resistant car cover film with a thickness of 400μm. The preparation method of the double-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows: Step 1: 20 g of N-methylpyrrolidone, 5 g of polyvinylpyrrolidone and 70 g of halloysite nanotubes were mixed and stirred to obtain a halloysite nanotube dispersion; Step 2: Mix ethyl orthosilicate and ethanol, add hydrochloric acid, stir and hydrolyze for 30 minutes to obtain a transparent solution; Step 3: adding the halloysite nanotube dispersion, mixing and stirring evenly to obtain a shell solution; the molar ratio of ethyl orthosilicate, ethanol and hydrochloric acid is 1:11:4.6; the volume ratio of the transparent solution to the halloysite nanotube dispersion is 1:1.5; Step 4: Take 90% N-methylpyrrolidone aqueous solution as the core layer solution; Step 5: electrospinning was performed using a coaxial electrospinning device. The electrospinning conditions were: voltage 20 kV, humidity 60%, outer diameter of the shell needle 1.4 mm, inner diameter 1.2 mm, outer diameter of the core needle 1.0 mm, inner diameter 0.7 mm, and a distance of 20 cm from the receiving plate to obtain an electrospinning membrane with a thickness of 50 μm. Step 6: Take out and dry, place in a programmed temperature furnace for calcination, heat to 650°C at a rate of 3°C / min and keep at that temperature for 3h, then continue to heat to 950°C at a rate of 5°C / min and keep at that temperature for 3h; Step 7: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain double-layer hollow membrane particles; Step 8: Take 10 g of double-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 9: Add 1.3 g of nano-titanium dioxide and 20 mL of ultrapure water, stir and mix with ultrasound at 40°C and 150 W for 1 h, let stand at room temperature for 12 h, and dry to obtain a double-layer hollow mesh membrane loaded with nano-titanium dioxide. Comparative Example 1 The difference between this comparative example and Example 2 is that: no halloysite nanotubes are added, and nano-silicon dioxide particles are used instead, as follows: A method for preparing a heat-insulating and scratch-resistant car cover film comprises the following steps, measured in parts by weight: S1: 12 parts of thermoplastic polyurethane, 6 parts of single-layer hollow mesh membrane loaded with nano-titanium dioxide and 0.03 parts of antioxidant 1076 were mixed, and the mixture was extruded and mixed in an internal mixer at 160°C; S2: put it into a screw extruder for extrusion. The screw extrusion conditions are as follows: the temperature from the feeding end to the die head is 65°C, 120°C, 180°C, 220°C, 220°C and 190°C respectively, the screw speed is 30rpm, and the film is cast to obtain a heat-insulating and scratch-resistant car cover film with a thickness of 300μm. The preparation method of the single-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows: Step 1: Take 20g N-methylpyrrolidone, 5g polyvinylpyrrolidone and 70g nano-silicon dioxide particles and mix them evenly to obtain a nano-silicon dioxide dispersion; Step 2: Mix ethyl orthosilicate and ethanol, add hydrochloric acid, stir and hydrolyze for 30 minutes to obtain a transparent solution; Step 3: Add nano-silica dispersion, mix and stir evenly to obtain a shell solution; the molar ratio of ethyl orthosilicate, ethanol and hydrochloric acid is 1:11:4.6; the volume ratio of the transparent solution and the halloysite nanotube dispersion is 1:1.5; Step 4: Take 90% N-methylpyrrolidone aqueous solution as the core layer solution; Step 5: electrospinning was performed using a coaxial electrospinning device. The electrospinning conditions were: voltage 20 kV, humidity 60%, outer diameter of the shell needle 1.4 mm, inner diameter 1.2 mm, outer diameter of the core needle 1.0 mm, inner diameter 0.7 mm, and a distance of 20 cm from the receiving plate to obtain an electrospinning membrane with a thickness of 50 μm. Step 6: Take out and dry, place in a programmed temperature furnace for calcination, heat to 650°C at a rate of 3°C / min and keep at that temperature for 3h, then continue to heat to 950°C at a rate of 5°C / min and keep at that temperature for 3h; Step 7: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain single-layer hollow membrane particles; Step 8: Take 10 g of single-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 9: Add 1.3 g of nano-titanium dioxide and 20 mL of ultrapure water, stir and mix with ultrasound at 40°C and 150 W for 1 h, let stand at room temperature for 12 h, and dry to obtain a single-layer hollow mesh membrane loaded with nano-titanium dioxide. Comparative Example 2 The difference between this comparative example and Example 2 is that the omentum is made into a single-layer hollow, as follows: A method for preparing a heat-insulating and scratch-resistant car cover film comprises the following steps, measured in parts by weight: S1: 12 parts of thermoplastic polyurethane, 6 parts of single-layer hollow mesh membrane loaded with nano-titanium dioxide and 0.03 parts of antioxidant 1076 were mixed, and the mixture was extruded and mixed in an internal mixer at 160°C; S2: put it into a screw extruder for extrusion. The screw extrusion conditions are as follows: the temperature from the feeding end to the die head is 65°C, 120°C, 180°C, 220°C, 220°C and 190°C respectively, the screw speed is 30rpm, and the film is cast to obtain a heat-insulating and scratch-resistant car cover film with a thickness of 300μm. The preparation method of the single-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows: Step 1: 20 g of N-methylpyrrolidone, 5 g of polyvinylpyrrolidone and 70 g of halloysite nanotubes were mixed and stirred to obtain a halloysite nanotube dispersion; Step 2: Mix ethyl orthosilicate and ethanol, add hydrochloric acid, stir and hydrolyze for 30 minutes to obtain a transparent solution; Step 3: adding the halloysite nanotube dispersion, mixing and stirring evenly to obtain an electrospinning solution; the molar ratio of tetraethyl orthosilicate, ethanol and hydrochloric acid is 1:11:4.6; the volume ratio of the transparent solution to the halloysite nanotube dispersion is 1:1.5; Step 4: electrospinning was performed using an electrospinning device. The electrospinning conditions were as follows: voltage of 20 kV, humidity of 60%, outer diameter of the needle of 1.4 mm, inner diameter of 1.2 mm, and distance from the receiving plate of 20 cm, to obtain an electrospinning membrane with a thickness of 50 μm; Step 5: drying after taking out, placing in a programmed temperature furnace for calcination, heating to 650°C at a rate of 3°C / min and keeping warm for 3 h, and then continuing to heat to 950°C at a rate of 5 / min°C and keeping warm for 3 h; Step 6: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain double-layer hollow membrane particles; Step 7: Take 10 g of double-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 8: Add 1.3 g of nano-titanium dioxide and 20 mL of ultrapure water, stir and mix with ultrasound at 40°C and 150 W for 1 h, let stand at room temperature for 12 h, and dry to obtain a double-layer hollow mesh membrane loaded with nano-titanium dioxide. Comparative Example 3 The difference between this comparative example and Example 2 is that no tetraethyl orthosilicate is added, and the details are as follows: A method for preparing a heat-insulating and scratch-resistant car cover film comprises the following steps, measured in parts by weight: S1: 12 parts of thermoplastic polyurethane, 6 parts of double-layer hollow mesh membrane loaded with nano-titanium dioxide and 0.03 parts of antioxidant 1076 were mixed, placed in an internal mixer and extruded and mixed at 160°C; S2: put it into a screw extruder for extrusion. The screw extrusion conditions are as follows: the temperature from the feeding end to the die head is 65°C, 120°C, 180°C, 220°C, 220°C and 190°C respectively, the screw speed is 30rpm, and the film is cast to obtain a heat-insulating and scratch-resistant car cover film with a thickness of 300μm. The preparation method of the double-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows: Step 1: Take 20g N-methylpyrrolidone, 5g polyvinylpyrrolidone and 70g halloysite nanotubes and mix them evenly to obtain a halloysite nanotube dispersion, which is a shell solution; Step 2: Take 90% N-methylpyrrolidone aqueous solution as the core layer solution; Step 3: electrospinning was performed using a coaxial electrospinning device. The electrospinning conditions were: voltage 20 kV, humidity 60%, outer diameter of the shell needle 1.4 mm, inner diameter 1.2 mm, outer diameter of the core needle 1.0 mm, inner diameter 0.7 mm, and a distance of 20 cm from the receiving plate to obtain an electrospinning membrane with a thickness of 50 μm. Step 4: Take out and dry, place in a programmed temperature furnace for calcination, heat to 650°C at a rate of 3°C / min and keep at that temperature for 3h, then continue to heat to 950°C at a rate of 5°C / min and keep at that temperature for 3h; Step 5: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain double-layer hollow membrane particles; Step 6: Take 10 g of double-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 7: Add 1.3 g of nano-titanium dioxide and 20 mL of ultrapure water, stir and mix with ultrasound at 40°C and 150 W for 1 h, let stand at room temperature for 12 h, and dry to obtain a double-layer hollow mesh membrane loaded with nano-titanium dioxide. The thermal conductivity of the sample was tested using a thermal conductivity meter using a transient hot wire test method according to GB / T 11205-2009. Each example was made into a 120mm×60mm sample, and tested 10 times at a speed of 3 minutes intervals, and the average value was taken; Scratch resistance: The car cover film prepared in each example was taken with the same size and shape area, fixed on a glass carrier, and a scratch test was performed under the same parameters using a scratch tester. After the scratch test, the surface of the material was cleaned and weighed, and the loss mass was recorded; The results are shown in Table 1 below: Table 1 The car cover film prepared in the above embodiment was cut into 1 cm×4 cm strips, and its mechanical properties were measured using a universal stretching machine with a loading speed of 2 mm / min and a stretching speed of 5 mm / min. The results are shown in Table 2: Table 2 Tensile strength(MPa) Elongation at break (%) Example 1 24.3 427 Example 2 24.2 425 Example 3 24.0 421 Example 4 24.0 423 Example 5 24.5 430 Example 6 22.8 409 Example 7 24.6 432 Example 8 23.7 414 Example 9 24.9 442 Comparative Example 1 24.7 433 Comparative Example 2 24.9 430 Comparative Example 3 22.0 406

Claims

1. A heat-insulating and scratch-resistant car cover film, characterized in that: The heat-insulating and scratch-resistant car cover film is based on thermoplastic polyurethane and has a double-layer hollow mesh membrane loaded with nano-titanium dioxide as filler; The mass ratio of the thermoplastic polyurethane to the double-layer hollow mesh membrane loaded with nano-titanium dioxide is 12:(5-7); The double-layer hollow mesh membrane loaded with nano-titanium dioxide is prepared by electrostatic spinning with halloysite nanotubes as raw materials and then loaded with nano-titanium dioxide.

2. The heat-insulating and scratch-resistant car cover film according to claim 1, characterized in that: The heat-insulating and scratch-resistant car cover film also includes antioxidants, which are antioxidant 245, antioxidant 1010, antioxidant 1076 and antioxidant 3114.

3. The heat-insulating and scratch-resistant car cover film according to claim 1, characterized in that: The thickness of the heat-insulating and scratch-resistant car cover film is 200-400 μm.

4. The heat-insulating and scratch-resistant car cover film according to claim 1, characterized in that: The preparation method of the double-layer hollow mesh membrane loaded with nano-titanium dioxide is as follows, in parts by weight: Step 1: Mix 20 parts of N-methylpyrrolidone, 5 parts of polyvinylpyrrolidone and 70 parts of halloysite nanotubes and stir them evenly to obtain a halloysite nanotube dispersion; Step 2: Mix ethyl orthosilicate and ethanol, add hydrochloric acid, stir and hydrolyze for 30 minutes to obtain a transparent solution; Step 3: Add the halloysite nanotube dispersion, mix and stir evenly to obtain a shell solution; Step 4: Take 90% N-methylpyrrolidone aqueous solution as the core layer solution; Step 5: Perform electrospinning using a coaxial electrospinning device to obtain an electrospinning membrane; Step 6: Take out and dry, place in a programmed temperature furnace for calcination, heat to 650-700°C at 3°C / min and keep at this temperature for 3h, then continue to heat to 900-1000°C at a rate of 5 / min°C and keep at this temperature for 3h; Step 7: Cool naturally to room temperature, take out, crush, and pass through a 170-mesh sieve to obtain double-layer hollow membrane particles; Step 8: Take 10 portions of double-layer hollow membrane particles, soak them in hydrochloric acid for 10 hours, wash them repeatedly with water, and dry them; Step 9: Add 1-1.5 parts of nano-titanium dioxide and 20 parts of ultrapure water, stir and mix with ultrasound at 40°C and 150W for 1 hour, let stand at room temperature for 12 hours, and dry to obtain a double-layer hollow mesh membrane loaded with nano-titanium dioxide.

5. The heat-insulating and scratch-resistant car cover film according to claim 4, characterized in that: The molar ratio of tetraethyl orthosilicate, ethanol and hydrochloric acid is 1:11:4.

6.

6. The heat-insulating and scratch-resistant car cover film according to claim 4, characterized in that: The volume ratio of the transparent solution to the halloysite nanotube dispersion is 1:(1-2).

7. The heat-insulating and scratch-resistant car cover film according to claim 4, characterized in that: The electrospinning conditions are as follows: voltage of 20 kV, humidity of 60%, outer diameter of shell needle of 1.4 mm, inner diameter of 1.2 mm, outer diameter of core needle of 1.0 mm, inner diameter of 0.7 mm, and distance from receiving plate of 20 cm.

8. The heat-insulating and scratch-resistant car cover film according to claim 4, characterized in that: The thickness of the electrospinning membrane in step 5 is 45-55 μm.

9. A method for preparing a heat-insulating and scratch-resistant car cover film according to any one of claims 1 to 8, characterized in that: The method comprises the following steps, in parts by weight: S1: Thermoplastic polyurethane, double-layer hollow mesh membrane loaded with nano-titanium dioxide and antioxidant are mixed, and placed in an internal mixer for extrusion mixing at 160°C; S2: Put it into a screw extruder, extrude it, and then perform tape casting to obtain it.

10. The method for preparing a heat-insulating and scratch-resistant car cover film according to claim 9, characterized in that: The screw extrusion conditions are as follows: the temperature from the feeding end to the die is 50-80°C, 80-145°C, 145-200°C, 180-245°C, 180-220°C and 170-210°C, and the screw speed is 25-40rpm.

Citation Information

Cited By

  • TPU (thermoplastic polyurethane) heat-insulating film for skylight and preparation process of TPU heat-insulating film

    CN120988323A

  • A sunroof tpu type heat insulation film and a preparation process thereof

    CN120988323B